2015
DOI: 10.1266/ggs.15-00038
|View full text |Cite
|
Sign up to set email alerts
|

Identification of A2059G 23S rRNA and G439A <i>rplC</i> gene mutations in <i>Streptococcus criceti</i> strain OMZ 61, a strain resistant to azithromycin, josamycin and clindamycin

Abstract: Streptococcus criceti is a cariogenic organism that belongs to the mutans streptococci. Of the four S. criceti strains, strain OMZ 61 has been identified as being resistant to erythromycin. Antimicrobial susceptibility testing showed that strain OMZ 61 is also resistant to azithromycin, josamycin and clindamycin but susceptible to tetracycline and tiamulin. DNA hybridization analysis of the 23S rRNA genes revealed that the hybridization patterns in strain OMZ 61 differed from those in the other three strains. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Similarly, point mutations in these ribosomal protein encoding genes have also been associated with acquired resistance to macrolides in Streptococcus criceti , S. pneumoniae , E. coli, and Brachyspira spp. [ 43 , 44 , 45 , 46 ]. Cross-resistance to more than one macrolide has been described in several bacterial species, such as Mycobacterium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, point mutations in these ribosomal protein encoding genes have also been associated with acquired resistance to macrolides in Streptococcus criceti , S. pneumoniae , E. coli, and Brachyspira spp. [ 43 , 44 , 45 , 46 ]. Cross-resistance to more than one macrolide has been described in several bacterial species, such as Mycobacterium sp.…”
Section: Discussionmentioning
confidence: 99%
“…RpsJ acts as general target of tigecycline adaption and a marker for alterations in antibiotic resistance in bacteria; the V57L mutation in rpsJ might cause weaker binding of tigecycline to 16S rRNA, leading to tigecycline resistance 45–48 . In RplD , encoding the ribosomal protein L4, it has also been found that the A2059G mutation confers resistance to macrolides and lincosamides 12, 4951 . Other genes relative to ribosomes, encoding ribosomal proteins, are also concerned with resistance.…”
Section: Discussionmentioning
confidence: 99%